Social Representation of School Success in Youth from Sinaloa: Hegemonic Elements vs. Concrete Practice - Pedro Damián Zamudio Elizalde; Maider Larrañaga Eguilegor; Fidencio López Beltrán (Universidad Autónoma de Baja California, 2021)
School success is both a political and social concern, but is often viewed from a reductionist, hegemonic rationale in which grades take center stage. This study aimed to gain deeper insight into the social representation of school success among high school students from Sinaloa, employing a structural approach to understand how this hegemonic rationale and its social insertions influence the representation of school success. The results show that these young people associate success with the archetypical successful, responsible student that makes an effort and shows interest. At the same time, they view learning from a practical standpoint, in which knowing how to use what has beenlearned is most important, rather than simply the grades earned. Also highlighted is the importance of the process and guidelines that enable students to stay in and complete high school. School success thus enables a better future.